Functional basis of poliovirus neutralization determined with monospecific neutralizing antibodies. - Emini, E A (1983)
Antibody-mediated poliovirus neutralization was studied by using a series of 13 monospecific neutralizing antibodies. These antibodies were found to recognize seven individual viral epitopes, several of which functionally overlap one another. Each epitope was capable of undergoing variation so that the variant virus was no longer capable of being neutralized by antibody directed against that epitope. The measured degree of variation for each site varied from -3.1 to -4.2 log10 variant PFU per wild-type PFU. Under nonsaturating but neutralizing conditions, the antibodies, with the exception of those directed to one specific epitope, failed to completely inhibit the virion's binding to the cell. Similarly, none of the neutralizing antibodies completely inhibited viral penetration, but all prevented virus-specific transcription. A strong correlation was established between the binding of each of the neutralizing antibodies, with one exception, to the virion and a significant shift in the virion's pI from 7.0 to ca. 4.0.